Maternal Impression Management in the Assessment of Childhood Depressive Symptomatology. Issue 5 (27th February 2018) - Lilly, Megan; Davis, Thompson E.; Castagna, Peter J.; Marker, Arwen; Davis, Allison B.
Abstract : Background: Self-report instruments are commonly used to assess for childhood depressive symptoms. Historically, clinicians have relied heavily on parent-reports due to concerns about childrens' cognitive abilities to understand diagnostic questions. However, parents may also be unreliable reporters due to a lack of understanding of their child's symptomatology, overshadowing by their own problems, and tendencies to promote themselves more favourably in order to achieve desired assessment goals. One such variable that can lead to unreliable reporting is impression management, which is a goal-directed response in which an individual (e.g. mother or father) attempts to represent themselves, or their child, in a socially desirable way to the observer.Aims: This study examined the relationship between mothers who engage in impression management, as measured by the Parenting Stress Index-Short Form defensive responding subscale, and parent-/child-self-reports of depressive symptomatology in 106 mother–child dyads.Methods: 106 clinic-referred children (mean child age = 10.06 years, range 7–16 years) were administered the Child Depression Inventory, and mothers (mean mother age = 40.80 years, range 27–57 years) were administered the Child-Behavior Checklist, Parenting Stress Index-Short Form, and Symptom Checklist-90-Revised.Results: As predicted, mothers who engaged in impression management under-reported their child's symptomatology on the anxious/depressed and withdrawn subscales of the Child Behavior Checklist. Moreover, the relationship between maternal-reported child depressive symptoms and child-reported depressive symptoms was moderated by impression management.Conclusions: These results suggest that children may be more reliable reporters of their own depressive symptomatology when mothers are highly defensive or stressed.